Pengaruh Think Talk Write Berbantuan Teori Jerome Bruner Terhadap Literasi Sains Siswa SD - Muslim, Mukhammad Arwani; Widodo, Wahono; Gunansyah, Ganes (Innovations in Multidisciplinary Education Journal, 2025)
Science literacy skills are essential skills that need to be developed since elementary school level. However, students' achievement of science literacy is often not optimal, so innovation in learning models is needed. This study aims to analyze the effect of implementing the Think Talk Write (TTW) learning model integrated with learning stages according to Jerome Bruner's theory on the science literacy skills of fifth grade elementary school students. Learning in this study was implemented using a teaching module that carries the theme of local culinary specialties of Porong, namely "Ote-Ote Porong", to provide a relevant context for students. This study used a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of fifth grade students at Sugihwaras Elementary School. The experimental group received treatment in the form of learning with the TTW model assisted by Bruner's theory using the "Ote-Ote Porong" teaching module, while the control group used conventional learning. Science literacy skills data were collected through test instruments (before and after treatment) and analyzed quantitatively using the ANCOVA statistical test. The results showed that there was a significant difference in increasing science literacy skills (p <0.05) between the experimental group and the control group. Students who learn with the TTW model assisted by Bruner's theory through contextual teaching modules show a higher increase in scientific literacy skills compared to students who learn with conventional methods. It is concluded that the Think Talk Write model assisted by Jerome Bruner's theory applied through local culinary-themed teaching modules is effective in improving the scientific literacy skills of fifth grade elementary school students.